Improving Mathematical Communication Ability and Self Regulation Learning Of Yunior High Students by Using Reciprocal Teaching - Abdul Qohar; Utari Sumarmo (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2013)
This paper presents the findings from a posttest experiment control group design by using reciprocal teaching, conducted in Indonesia University of Education to investigate students' ability in mathematical communication and self regulated learning. The subject of the study were 254 of 9th grade students from three junior high schools of the high, medium, and low level in Bojonegoro, East Java.Â The instruments of the study were an essay mathematical communication test, and a self-regulated learning scale. The study found that reciprocal teaching took the best role among school cluster and students' prior mathematics ability on students' mathematical communication ability and self-regulated learning as well. The other finding was there was an interaction between school cluster and teaching approaches, but was no interaction between students' prior mathematics ability and teaching approaches on mathematical communication ability and self-regulated learning. Moreover, there was an association between mathematical communication and self regulated learning.